Laporan Kasus : Katarak Senilis Matur Occuli Dextra - Raidatul Aufa; Fauzan T. Banta (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
A 55-year-old female patient came to F Hospital complaining of blurred vision in her left eye for 3 years and a gradual decrease in vision. The vision in her left eye had been increasingly blurry and disrupting activities for 4 months before coming to the hospital. The patient reported discomfort and blurriness when looking at a distance, but there was no disturbance in close-up vision. The patient also reported foggy vision and glare, especially during the day. The patient did not complain of dizziness, nausea, or vomiting. When looking at objects, there was no change in size, and she had never seen floating objects. The patient had undergone cataract surgery on her right eye 2 months ago. She had a history of type 2 diabetes mellitus since 2017 and was regularly taking antidiabetic medication. The patient reported wearing glasses for 3 years. The general status was normal, while the left local status showed 2/60 vision, arcus senilis (+), cloudy lens, and shadow test (-). Fasting blood sugar examination showed hyperglycemia, and tonometry showed increased intraocular pressure. Based on this, the patient was diagnosed with a mature senile cataract of the left eye. The patient underwent surgery on the left eye using phacoemulsification and has a good prognosis. Appropriate cataract management can significantly improve the patient's quality of life.